Climate and nutri-smart agricultural bundles for vulnerable and host populations to improve nutrition and livelihoods - Misra, Rewa S.; Ambler, Kate (CGIAR System Organization, 2024)
This innovation provides a bundle of climate and nutri-smart inputs to vulnerable and host populations in a fragile setting, with the intention of improving the nutritional and resilience outcomes of the recipients. The bundle includes biofortified seed, fertilizer, pesticide, and insurance. Selected farmers will receive a voucher for 50% of the value of bundle. The goal of this project is to provide a sustainable way for vulnerable people to sustainably improve their nutrition and livelihoods.